Prospects for the Development of International Tourism - Georgieva, Ralitsa (Research Papers, 2025)
The purpose of the current article is to identify the direction for development of the international tourism, with the idea of creating practical-applied benefits for the tourism business and highlighting opportunities for development. The tasks are related to establishing the importance and view on the condition of international tourism, as well as to identifying trends that will provide direction for the development of the activities of tourist enterprises and destinations. The methods used to achieve the research purpose are deductive and inductive, with the aim of solving the set tasks, the solution of which will lead to the achievement of scientific and practical results and contributions. The results of the research aim to establish direction of development of the international tourism, with the applicability for the tourism business.